Optimizing The Community Role In The PBPH ULM Mangrove Area by Creating A Demonstration Plot For Soft Shell Crab Cultivation Using Recirculating Aquaculture System Method: Optimalisasi Peran Masyarakat Di Kawasan Mangrove PBPH ULM Melalui Pembuatan Demplot Usaha Budidaya Kepiting Soka Dengan Metode Recirculating Aquaculture System - Frans Tony; Indira Fitriliyani; Yuliyanto; Bahruddin Yusuf (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The program to create environmentally friendly and sustainable soka crab cultivation demonstration plots is a strategic step to increase the capacity of coastal communities in Kotabaru Regency. The application of the RAS (Recirculating Aquaculture System) method using a vertical crab house allows for efficient use of resources and better waste management. This community service activity is directed towards these interests through the Forest Utilization Business Permit Commitment Approval Letter (PBPH) for Lambung Mangkurat University (ULM). The implementation method is divided into five main stages which are carried out systematically and sequentially, namely preparation, implementation, and reporting. The results of the activity have a positive impact on the people of Teluk Tamiang Village and fishermen in Kotabaru Regency in improving their standard of living and economic welfare. Based on the results of the evaluation that has been carried out, it is recommended to continue coaching and mentoring, as well as expanding the scope of the demonstration plot to other groups or villages that have the same potential. In addition, further studies are needed regarding the optimization of the use of the RAS method using a vertical crab house as a medium for soka crab cultivation.